Legal Protection on Data Transmission Through the Digital Short Message Platform - Evelyn Angelita Pinondang Manurung; Eka Ayu Purnama Lestari (Warmadewa Press, 2022)
Digital media is currently utilized by the entire community because it has provided its own space digitally for its users to move in terms of communication and various activities. Especially in terms of communication today people prefer digital media / platforms in sending short messages for information or data delivery activities. The ability to send fast, easy and equipped with service features as per the needs of its users becomes an effective choice for the public in using digital short message platforms. The use of digital messaging platforms today also makes people begin to realize the importance of security in data transmission. The high activity of people who send personal data through digital platforms must also be balanced with the level of security and confidentiality of data on the platform. This research aims to find out the legal protection arrangements in the delivery of data through digital messaging platforms so that the wider community understands security and data protection. This research uses normative juridical research methods using the legal sources of literature. The wider community today sees the number of cases of data violations / misuse through digital messaging platforms is clear evidence that personal data is a human right of digital platform users that must be protected. Therefore, it is necessary to have legal tools that can accommodate the form of laws to ensure the security and protection of personal data.